OPTIMALISASI DAN STRATEGI PENYEDIAAN AIR MINUM PT. AIR MINUM INTAN BANJAR (PERSERODA) WILAYAH PELAYANAN GAMBUT - Januarianto, Agung; Rahman, Mijani; Lilimantik, Emmy; Fatmawati, Fatmawati (Universitas Lambung Mangkurat, 2023)
PT. Air Minum Intan Banjar (Perseroda) as a drinking water manager is required to fullfill the water needs of the society in Banjarbaru and Banjar Regency. It is necessary to study the optimization and drinking water supply strategy of PT. Air Minum Intan Banjar Specifically for Gambut Service Area. The purpose of this research is to optimize and to formulate a drinking water supply strategy for the people who are included in the Gambut service area of PT. Air Minum Intan Banjar (Perseroda). The method used in this research is to collect primary and secondary. Data analysis used descriptive qualitative and quantitative analysis. The place of research PT. Air Minum Intan Banjar (Perseroda) Gambut service area. The results showed that during the existing conditions and service development, the drinking water supply system was not optimal. For this reason, optimization steps and strategies for drinking water supply. Optimization can be carried out by reducing leakage, increasing the water supply, increasing the pressure at the connection points and changing the diameter of the pipes and changing the dimensions of the Gambut Booster. The drinking water supply strategy can be carried out by maintaining the continuity of the existing water supply, controlling leaks, modifying the pipelines system as well as carrying out pipe washing.